Video Edukasi Vaksinasi Covid 19 - Said Hi Abbas; Lita Asyriati Latif; Bambang Tjiroso (Patria Artha Journal of Community (PKM), 2022)
This corona virus vaccination educational video aims to provide correct information to the public and the importance of vaccination to prevent the spread of the corona virus. The educational video will also contain information on the types of covid 19 vaccines that have been and will be imported by the government of the Republic of Indonesia, the stages of vaccination and the number of vaccines to be given as well as the HALAL certification that has been given by the MUI. The making of this video itself is carried out in several stages, including making a video script that will be taken where at this stage a script or video capture flow will be made, determining the artist who will be included in the video and the location for taking the video. The next stage is Video Capture where several videos will be taken such as; a. Video retrieval of lecturers' vaccination process, b. Taking an explanatory video about Vaccination c. Video taking of the invitation to the Covid 19 vaccination and the taking of videos of people who have vaccinated against Covid 19. The third stage is video editing, which will merge and edit the videos that have been taken and the last stage is publishing through several social media, including Facebook, Instagram and Whatsapp. Keywords: Covid 19 Vaccine, Halal and safe Vaccine, Educational Video